Effect of gas-timing technique on structure and optical properties of sputtered zinc oxide films - Don Klaitabtim (2018)
Zinc oxide thin films were prepared by the RF magnetron sputtering using a gas-timing technique whereby the flow of argon into the sputtering chamber was controlled by an on-off sequence. With this technique, polycrystalline ZnO thin films on glass substrates have been achieved without any thermal treatment of the substrate. In addition, the RF power and the gas-timing sequence can be fine-tuned to produce the hexagonal structure of ZnO thin films. X-ray diffraction (XRD) measurements confirm a (0 0 2) plane oriented wurtzite structure ZnO thin films. The optimized conditions for this hexagonal structure are an RF power of 30 W and an on-off gas-timing sequence of 50:2 s. The root mean square surface roughness of ZnO thin films measured by atomic force microscopy are in the range of 6.4-11.5 nm. The optical transmittance of ZnO thin films is over 85% in the visible range. © 2007 Elsevier Ltd and Techna Group S.r.l.